Contribution of Ferromagnetic Medium to the Output of Triboelectric Nanogenerators Derived from Maxwell's Equations. Issue 21 (27th March 2021) - Li, Yahui; Li, Guizhong; Zhang, Penglei; Zhang, Haodong; Ren, Chao; Shi, Xian; Cai, Han; Zhang, Yanxin; Wang, Yusen; Guo, Zhanfeng; Li, Hongfang; Ding, Guifu; et al.
Abstract: Triboelectric nanogenerators (TENGs) use the displacement current as a driving force to convert mechanical energy into electric power, which has made great contributions to micro‐nano energy harvesting, self‐powered systems, and the sustainable development of mankind. To date, it is accepted that the output of TENGs is only dependent on the polarization effect. This study reveals that this view is incomplete and, in reality, the magnetization effect also makes a significant contribution to the output of TENGs. For the first time, a novel insight on the output of TENGs is discovered through the theoretical derivation and analysis of Maxwell's equations in ferromagnetic medium. Experimentally, TENGs based on ferromagnetic media are constructed, which exhibit higher output than that of non‐ferromagnetic media based. Interestingly, the output behavior of ferromagnetic media based TENGs is strongly related to the external magnetic field ambient, which is well demonstrated. The discovered output characteristics of TENGs are precisely derived from the working principle of TENGs, simultaneously, a completed and unified theoretical system is constructed for TENGs. This significant discovery and theory will be an indispensable supplement to the existing research on TENGs and also provide a general guidance and deeper understanding of the TENG. Abstract : Based on Maxwell's equations, the output characteristics of triboelectric nanogenerators (TENGs) are theoretically deduced and experimentally verified, which include both polarization and magnetization effects. For the first time, the discovered output characteristics of TENGs is precisely derived from the working principle of TENGs, simultaneously, a complete and unified theoretical system is constructed for TENGs.